Neonatal Sepsis Alters the Excitability of Regular Spiking Cells in the Nucleus of the Solitary Tract in Rats. Issue 2 (August 2020) - Eftekhari, Golnar; Shojaei, Amir; Raoufy, Mohammad R.; Azizi, Hossein; Semnanian, Saeed; Mani, Ali R.
ABSTRACT: Objective: Sepsis is a leading cause of mortality and morbidity in infants. Although the measures of autonomic dysfunction (e.g., reduced heart rate variability) predict mortality in sepsis, the mechanism of sepsis-induced autonomic dysfunction has remained elusive. The nucleus of the solitary tract (NTS) is a vital structure for the integrated autonomic response to physiological challenges. In the present study we hypothesized that sepsis alters the excitability of NTS neurons in a rat model of neonatal sepsis (14-day-old rats). Methods and Results: Sepsis was induced by intraperitoneal injection of cecal slurry (CS) in rat neonates. The presence of autonomic dysfunction was confirmed by observing a significant reduction in both short-term and long-term heart rate variably following CS injection. We investigated the effect of polymicrobial sepsis on the electrophysiological properties of the medial NTS neurons using a whole cell patch clamp recording. Our results showed that the resting membrane potential in regular spiking neurons was significantly less polarized in the septic group (−37.6 ± 1.76 mv) when compared with the control group (−54.7 ± 1.73 mv, P  < 0.001). The number of spontaneous action potentials in the septic group was also significantly higher than the control group ( P  < 0.05). In addition, the frequency and amplitude of the spontaneous excitatory post synaptic potentials was significantly higher in neurons recorded in the septic group ( P  < 0.001). Interestingly, regular spiking cells in the CS group exhibited a rebound action potential following hyperpolarization. Injection of depolarizing currents was associated with lower first spike latency and changes in rise slope of action potential ( P  < 0.001). Conclusions: We showed that polymicrobial sepsis increases the excitability of regular spiking cells in the medial NTS. These alterations can potentially affect neural coding and thus may contribute to an abnormal homeostatic or allostatic physiological response to sepsis and systemic inflammation. Abstract : Supplemental Digital Content is available in the text